Low-Noise Voltage Controlled Oscillator with Coupled Microstrip Lines of Different Lengths - Aleksander V. Baranov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Coupled two- or three-wire microstrip lines are often used to reduce a phase noise of voltage-controlled oscillators (VCOs). Unfortunately, the phase noise was not optimized depending on the lengths of a three-wire coupled microstrip lines.Aim. For the three-wire coupled microstrip structure, the task of determining of the optimal lengths of its stabs was set. The stabs were corresponded to the reduced phase noise of the selected VCO.Materials and methods. In the oscillator example, the resonator model with three electromagnetically coupled microstrip lines was studied. Herein the second line from the first and the third from the second line differed by the same physical length. The widths of the first and of the third lines were the same, and their coupling clearances with the second line were the same too. On the one hand, in this three-wire microstrip line short-end modes with a common ground electrode were implemented. On the other, at the ends of the first and of the third lines open-end modes were implemented. The free end of the second line is line input.Results. For the considered oscillator, the basic formulas for calculating its frequency-setting elements and resonator model parameters were obtained. By these formulas the estimation of base contours impedances for two oscillators with three-coupled microstrip lines of the same and different lengths, and also for the oscillator using a two-coupled microstrip line was given. For comparison, the proposed VCO near the optimal difference in the three-wire line microstrips lengths had the base contour impedance phase steepness 2...4 times greater, as well as its modules graphs had the width 4...10 times less.Conclusion. In comparison with the known VCOs, the possibility of obtaining lower phase noise spectrum levels at 6...10 dB/Hz in the designed oscillator with the calculated lengths of the selected three-coupled line microstrips was experimentally confirmed.